2013
DOI: 10.1002/adhm.201200214
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Micro‐ and Nanofabrication for Medicine

Abstract: This manuscript constitutes a review of several innovative biomedical technologies fabricated using the precision and accuracy of silicon micro- and nanofabrication. The technologies to be reviewed are subcutaneous nanochannel drug delivery implants for the continuous tunable zero-order release of therapeutics, multi-stage logic embedded vectors for the targeted systemic distribution of both therapeutic and imaging contrast agents, silicon and porous silicon nanowires for investigating cellular interactions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 338 publications
(333 reference statements)
0
55
0
1
Order By: Relevance
“…[52] The latter development of micro-and nanofabrication techniques led to an increase in experimental setups using micro-and nanopatterns for in vitro studies. [53][54][55] The cellular response to the surface nanotopography and its correlation to the surface-bound proteins have been highlighted by Lim et al who showed that cell adhesion was unaffected by surface nanotopography if performed in the absence of serum. [56] This was a very important finding which allowed speculations that implant surfaces should be designed not for cells but more prominently for proteins as primary targets.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…[52] The latter development of micro-and nanofabrication techniques led to an increase in experimental setups using micro-and nanopatterns for in vitro studies. [53][54][55] The cellular response to the surface nanotopography and its correlation to the surface-bound proteins have been highlighted by Lim et al who showed that cell adhesion was unaffected by surface nanotopography if performed in the absence of serum. [56] This was a very important finding which allowed speculations that implant surfaces should be designed not for cells but more prominently for proteins as primary targets.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%
“…29,61 Ultrathin, nanofabricated membrane filters, such as nanoporous silicon and silicon nitride, offer significant advantages over conventional polymer ultrafiltration membranes. 54,[62][63][64][65][66][67][68][69][70] Mechanically robust, unsupported ultrathin filters allow for high hydraulic and diffusive permeabilities. The material properties and ultrathin dimensions allow for the straightforward fabrication of smooth pores in controllable, welldefined sizes with narrow size distributions, and with high areal densities.…”
mentioning
confidence: 99%
“…8 Copyright: American Scientific Publishers approaches are limited in that a polydisperse blend is often generated. [9][10][11] Further compounding the issue, traditional methods for separating populations of nanoparticles with little variation in size [12][13][14] are unlikely to be applicable to SiNPs due to their small size (<5 nm in diameter) and light density (∼1400 g/cm 3 . 15 Specifically, while centrifugation provides the most direct approach to obtain the desired products, the size and density of SiNPs does not allow for the efficient isolation of different NP subpopulations.…”
Section: Introductionmentioning
confidence: 99%